Laser ablation of the pia mater for insertion of high-density microelectrode arrays in a translational sheep model. (11th June 2021) - Boergens, Kevin M; Tadić, Aleksandar; Hopper, Matthew S; McNamara, Ingrid; Fell, Devin; Sahasrabuddhe, Kunal; Kong, Yifan; Straka, Malgorzata; Sohal, Harbaljit S; Angle, Matthew R
Abstract: Objective . The safe insertion of high density intracortical electrode arrays has been a long-standing practical challenge for neural interface engineering and applications such as brain–computer interfaces (BCIs). However, the pia mater can be difficult to penetrate and causes deformation of underlying cortical tissue during insertion of high-density intracortical arrays. This can lead to neuron damage or failed insertions. The development of a method to ease insertion through the pia mater would represent a significant step toward inserting high density intracortical arrays. Approach . Here we describe a surgical procedure, inspired by laser corneal ablation, that can be used in translational models to thin the pia mater. Main results . We demonstrate that controlled pia removal with laser ablation over a small area of cortex allows for microelectrode arrays to be inserted into the cortex with less force, thus reducing deformation of underlying tissue during placement of the microelectrodes. This procedure allows for insertion of high-density electrode arrays and subsequent acute recordings of spiking neuron activity in sheep cortex. We also show histological and electrophysiological evidence that laser removal of the pia does not acutely affect neuronal viability in the region. Significance . Laser ablation of the pia reduces insertion forces of high-density arrays with minimal to no acute damage to cortical neurons. This approach suggests a promising new path for clinical BCI with high-density microelectrode arrays.